Determination Potential Experts by Application The Apriori Algorithm and the K-Means Algorithm - Sovia, Rini; Defit, Sarjon; Fatimah, Noor (International Journal of Artificial Intelligence Research, 2022)
Experts are people who have special expertise who provide services based on their expertise. The company has experts in handling projects that will be carried out for the progress of the company. The importance of the quality of experts in the company can improve the quality of human resources. The Apriori algorithm is a data mining method that has the aim of looking for association patterns based on the project being carried out so that they can be identified by experts who are often used in handling projects. Furthermore, a data mining approach is needed to classify experts with the K-means algorithm used. This study combines the Apriori and K-means algorithms, by grouping experts based on the handling of the project they are working on.